Another look at reactions of 4-hydroxycoumarin with hydroxyl radical in the environment: deprotonation and diffusion effects. (7th September 2021) - Vo, Quan V.; Thi Hoa, Nguyen; Mechler, Adam
Abstract : Quantum chemistry calculations suggest that chemical fate of the anticoagulant rodenticide 4-hydroxycoumarin in the environment is crucially dependent on deprotonation in aqueous medium. Abstract : Coumarins are important chemical precursors for the synthesis of anticoagulants used as human medicines as well as rodenticides. Environmental discharge of these coumarin derivatives, commonly known as 4-hydroxycoumarins, is therefore a major concern. Advanced oxidative processes (AOP) are radical reactions of toxic contaminants with environmental free radicals, ideally leading to less toxic products. Therefore, the study of these processes is of key importance for a better understanding of the chemical transformations and long term environmental effect of toxic discharges. Here the AOP of the unsubstituted 4-Hydroxycoumarin (4HC ), the parent compound of the drugs and pesticides, is studied with HO˙ radical in aqueous and lipidic environments, using quantum chemical methods. Two reaction steps were modelled by considering the fundamental radical reactions of phenolic compounds as established before. Particular attention is paid to the reactions in aqueous environment. Thermodynamic and kinetic calculations were performed, assessing the likelihood and contribution of each possible reaction path to yield the most likely products. Previous works on AOP of 4HC neglected the deprotonation of the acidic moiety and the diffusion limits of the solvent. Here these points are addressed, predicting a different set of intermediate and final products. Toxicity tests predict that the main products are less toxic than 4HC . Our results demonstrate the importance of aqueous environment in the chemical fate of toxins in the environment.